The role of exercise and nutrition in modulating inflammatory cytokines activity for obesity management - Sobreviela Sánchez, Sara; Giusfredi Quevedo, Ravi; Fernandes, Tiago; da Fonseca, Guilherme Wesley Peixoto (Frontiers in Endocrinology, 2025)
Obesity is recognized as a systemic disease characterized by chronic, low-grade inflammation. The persistent inflammatory state can be driven by secretion of cytokines from adipose tissue, also known as adipokines. In patients with obesity, adipose tissue releases elevated levels of pro-inflammatory cytokines that can have an autocrine and paracrine function. The main cytokines involved in this process include tumor necrosis factor alpha (TNF-α), interleukin-6, and interleukin-1 beta (IL-1β). These molecules actively contribute to metabolic dysregulation by interfering with insulin signaling pathways and facilitating the infiltration of immune cells into adipose tissue. Thus, a vicious cycle can be established in which inflammation perpetuates metabolic disturbances, increasing the risk of developing cardiovascular disease, type II diabetes mellitus, and other chronic conditions. On the other hand, physical exercise can release myokines with anti-inflammatory properties, such as interleukin-6 and irisin, which can positively modulate immune response. Regular physical activity and healthy eating patterns emerge as essential tools to counteract low-grade inflammation. A diet rich in bioactive compounds, such as antioxidants and polyunsaturated fatty acids, may also regulate cytokine expression, reinforcing the role of nutrition as a therapeutic strategy for obesity management. In conclusion, the role of inflammatory cytokines in obesity is central and managing their activity through non-pharmacological interventions, combining exercise and nutrition, represents a powerful tool to prevent long-term complications. However, more studies are needed to elucidate the exact molecular mechanisms by which nutrition and exercise modulate inflammation in obesity, in order to develop more effective interventions.